Risk factors associated with suicide among kidney cancer patients: A Surveillance, Epidemiology, and End Results analysis. (11th July 2019) - Guo, Chenyu; Zheng, Wenwen; Zhu, Weiwei; Yu, Shengqiang; Ding, Yuexia; Wu, Qingna; Tang, Qiling; Lu, Congxiao
Abstract: Background: The suicide risk was higher in kidney cancer patients than in the general population. The purpose of this study was to characterize the suicide rates among kidney cancer patients and to identify the potential risk factors associated with suicide from the Surveillance, Epidemiology, and End Results (SEER) database. Methods: Kidney cancer patients were identified from the SEER database during 1973‐2015. Suicide rates and standardized mortality ratios (SMRs) of this population were calculated, and the US general population during 1981‐2015 was chosen as a reference. Univariable and multivariable Cox regression were performed to find out potential risk factors of suicide. Results: There were 207 suicides identified among 171 819 individuals with kidney cancer observed for 948 272 person‐years. The suicide rate was 21.83 per 100 000 person‐years, and SMR was 1.83 (95% CI: 1.59‐2.10). On Cox regression, diagnosis in early years (1973‐1982 vs 2003‐2015, HR: 2.03, 95% CI: 1.01‐4.11, P  = 0.048; 1983‐1992 vs 2003‐2015, HR: 1.99, 95% CI: 1.18‐3.35, P  = 0.010), male sex (vs female sex, HR: 4.43, 95% CI: 2.95‐6.65, P  < 0.001), unmarried status (vs married status, HR: 2.54, 95% CI: 1.91‐3.38, P  < 0.001), non‐black race (white race vs black race, HR: 4.47, 95% CI: 2.09‐9.58, P  < 0.001; other races vs black race, HR: 3.01, 95% CI: 1.08‐8.37, P  = 0.035), higher histologic grade (grade IV vs grade I, HR: 3.27, 95% CI: 1.50‐7.13, P  = 0.003; grade III vs grade I, HR: 2.13, 95% CI: 1.19‐3.81, P  = 0.011) and cancer‐directed surgery not performed (vs performed, HR: 2.78, 95% CI: 1.52‐5.11, P  < 0.001) were independent risk factors of suicide among kidney cancer patients. Conclusions: Diagnosis in early years, male sex, unmarried status, non‐black race, higher histologic grade, and cancer‐directed surgery not performed were significantly associated with suicide among kidney cancer patients. In order to prevent suicidal death, clinicians should pay more attention to patients with high‐risk factors of suicide. Abstract : The suicide rate of kidney cancer patients selected from the SEER database between 1973 and 2015 was 21.83 per 100 000 person‐years, and standardized mortality ratio was 1.83 (95% CI: 1.59‐2.10). Diagnosis in early years, male sex, unmarried status, non‐black race, higher histologic grade, and cancer‐directed surgery not performed were significantly associated with suicide among patients with kidney cancer.